2022
DOI: 10.1109/tqe.2022.3160015
|View full text |Cite
|
Sign up to set email alerts
|

Topological-Graph Dependencies and Scaling Properties of a Heuristic Qubit-Assignment Algorithm

Abstract: The qubit-mapping problem aims to assign and route qubits of a quantum circuit onto a NISQ device in an optimized fashion, with respect to some cost function. Finding an optimal solution to this problem is known to scale exponentially in computational complexity; as such, it is imperative to investigate scalable qubit-mapping solutions for NISQ computation. In this work, a noise-aware heuristic qubit-assignment algorithm (which assigns initial placements for qubits in a quantum algorithm to qubits on a NISQ de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Our work also shows that much optimization is left at the level of quantum compilation before running stabilizer circuits on hardware; indeed, several studies have shown that topological-graph properties associated with circuit-level qubit interactions play an important role in suppressing errors for NISQ-era algorithms [32]- [35], and error-correction algorithms are no exception. It would be interesting to evaluate whether such lower-depth syndrome-extraction sequences as ours would be amenable still to NISQ-era devices, given their restricted connectivity, and whether or not current strategies such as parallel syndrome extraction [10] could be utilized for further gate reductions.…”
Section: Discussionmentioning
confidence: 70%
“…Our work also shows that much optimization is left at the level of quantum compilation before running stabilizer circuits on hardware; indeed, several studies have shown that topological-graph properties associated with circuit-level qubit interactions play an important role in suppressing errors for NISQ-era algorithms [32]- [35], and error-correction algorithms are no exception. It would be interesting to evaluate whether such lower-depth syndrome-extraction sequences as ours would be amenable still to NISQ-era devices, given their restricted connectivity, and whether or not current strategies such as parallel syndrome extraction [10] could be utilized for further gate reductions.…”
Section: Discussionmentioning
confidence: 70%
“…The maintenance phase includes changes, modifications, and updates to the customer-related QSE. QC is a trending area for research in QSE, focusing mainly on classical software systems integrated with quantum algorithms [23]. Quantum Computers are more cost-effective to design because they adopt existing classical software systems.…”
Section: Deployment and Maintenance Phasementioning
confidence: 99%
“…However, solving the quantum circuit mapping problem for a large number of qubits can be computationally unfeasible, even for contemporary single-core devices. To tackle it, diverse mapping algorithms have been proposed, including heuristic or brute-force strategies, graph-theoretical techniques, dynamic programming algorithms, and machine learning-based solutions [2,7,10,[17][18][19][20][21][22][23][24].…”
Section: Background and Related Workmentioning
confidence: 99%
“…In order to improve their initial approach in terms of circuit and graph partitioning with an overly-restricting local lookahead function, we rely on previous subgraph isomorphism- [21,24,[30][31][32] and QUBO optimization-based single-core solutions [33,34] where now instead of mapping logical qubits to optimal subsets of coupling graph representing the physical qubits and their connections (Fig. 1) we map qubits to different cores.…”
Section: Background and Related Workmentioning
confidence: 99%